URBAN LIFESTYLE AND ENVIRONMENTAL AWARENESS AS PREDICTORS OF OUTDOOR APPAREL CONSUMPTION AMONG NATURE LOVER STUDENTS - Didit Darmawan; Amelia Pristian Syah Putri (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
This study examines the influence of urban lifestyle and environmental awareness on outdoor apparel consumption among students who are members of the Nature Lovers Student Activity Unit in Surabaya, Malang, and Sidoarjo. A quantitative explanatory approach was used. Data were collected from 100 respondents using a Likert-scale questionnaire and analyzed using multiple linear regression after classical assumption tests. Urban lifestyle has a positive and significant effect on outdoor apparel consumption. Environmental awareness also has a positive and significant effect. Simultaneously, both variables significantly influence consumption, explaining 44.2% of its variance. Findings support the Theory of Planned Behavior, Value-Belief-Norm Theory, and Consumer Culture Theory, offering insights for marketers and student activity unit managers.